Integrating Islamic Law and Modern Regulation: Cryptocurrency as a Sharia-Compliant Digital Asset in Indonesia - Mokodompis, Iin Indriani; Pedju, Rizaldy Purnomo; Muhammad, Adamu Abubakar (ANTMIND YOUTH EMPOWER FOUNDATION, 2024)
Cryptocurrency, as a rapidly evolving digital asset, has sparked significant debates regarding its legality and compliance with Islamic law. This study examines the intersection of Indonesian positive law and Islamic principles in regulating cryptocurrency as a tradable commodity (Sil’ah). Using a qualitative library research approach, the research explores regulatory frameworks such as Peraturan Menteri Perdagangan Nomor 99 Tahun 2018 and Peraturan BAPPEBTI Nomor 5 Tahun 2019, alongside Islamic legal standards for Sil’ah. Findings reveal that while Indonesian law has established a robust regulatory system ensuring transparency and security, compliance with Islamic principles requires further alignment, particularly in addressing challenges like volatility, lack of physical form, and potential gharar (uncertainty). However, digital documentation and blockchain technology provide opportunities for cryptocurrency to meet Sil’ah criteria, including ownership clarity and economic utility. The study emphasizes the potential for harmonizing positive law and Islamic law through adaptive regulations and innovative technologies such as blockchain-based smart contracts and halal asset tokenization. This integration could support a sharia-compliant digital economy, fostering inclusivity and trust among Muslim investors. The research contributes to bridging gaps in understanding cryptocurrency's role within Islamic finance and its future in the global economic landscape.